Myocardial Injury in Critically Ill Children: A Case Control Study - Hassan, Basheir (Hindawi Publishing Corporation, 2014)
Objectives. The aim of this study was to investigate the occurrence of myocardial injury in critically ill children through assessment of cardiac troponin T levels and whether levels are associated with disease severity and myocardial dysfunction measured by echocardiography. Methods. Over a 6-month period, this case control study included 50 patients admitted to Pediatric Intensive Care Unit of Zagazig University Children's Hospital. Twenty-five healthy children were included as a control group. Demographic and clinical data including the pediatric index of mortality II score were recorded. Echocardiographic examination was done and level of cardiac troponin T was measured using Elecsys Troponin T STAT Immunoassay. Results. Cardiac troponin T levels were significantly higher in critically ill in comparison to healthy children (median 22 (18–28) pg/mL versus 10 (10-10) pg/mL, P < 0.05). Cardiac troponin T levels correlated positively with duration of ventilation as well as with disease severity and correlated negatively with left ventricular fractional shortening. Moreover, cardiac troponin T levels were significantly higher in nonsurvivors when compared to survivors (median 34.5 (27.5–41.5) pg/mL versus 20 (18–24) pg/mL, P < 0.05). Conclusion. In critically ill children, cardiac troponin T levels were elevated and were associated with duration of ventilation and disease severity.